Journey Through Despair, 1880-1914 - Lester, John Ashby (Book collections on Project MUSE., 2016)
English literary culture from the death of Thomas Carlyle to the First World War was paradoxical and diverse. In literature it was a time of confusion and a nervous, often frenzied, search for new terms on which the imagination could live. Professor Lester shows that the literary culture of the period moved steadily from a suspicion that the old bases of significant imaginative life were indefensible to a widespread conviction that they had collapsed. His book is not an exercise in literary criticism. Rather, it is an attempt to discover the "geist" of an age, to provide a synthesis for the years 1880-1914. His overriding concern is: "What is the primary force which so unsettles, disperses, and disorients the imaginative experience of this period?"Originally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.